The Role of the Regional Regulations of the West Sulawesi Province in Protecting the Local Wisdom of the Massau’ Tradition in the Mandar Tribe - Astomo, Putera Astomo; AH, Arfhani Ichsan; Mohd Khambali, Khadijah binti (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2024)
The issue related to the Massau’ Tradition is the lack of coordination between the regional government and the village government, resulting in the failure to socialize regional regulations on river management and utilization to the public. As a result, the Mandar people do not understand their rights, obligations, and prohibitions regarding river use, even though the Massau’ Tradition is closely linked to Islam, culture, and customs. Furthermore, the village government has not taken firm action against those who damage the environment around the river. This study aims to answer two questions: 1) How is the local wisdom of the Massau’ Tradition manifested by the Mandar Tribe? 2) What is the role of regional regulations in protecting the local wisdom of the Massau’ Tradition of the Mandar Tribe? The methods used are a legislative approach and legal sociology. The research results show that the local wisdom of the Massau’ Tradition in the Mandar Tribe is manifested through Panggaukang Ma’guna, Siola-ola, Pau Macoa, and Manjagai. The role of regional regulations in protecting this local wisdom is reflected in several aspects, such as the protection and management of the river environment, the Coastal Area and Small Island Zoning Plan, and the implementation of public order and tranquility by prioritizing customary and social norms, especially those that apply to the Mandar Tribe.